Palladium-catalyzed [2 + 2 + 1] annulation: access to chromone fused cyclopentanones with cyclopropenone as the CO source. Issue 12 (20th April 2021) - Zhu, Wen-Qing; Fang, Yu-Chen; Han, Wen-Yong; Li, Fei; Yang, Min-Ge; Chen, Yong-Zheng
Abstract : A variety of chromone fused cyclopentanones are efficiently generated in good to high yields via palladium-catalyzed [2 + 2 + 1] annulation, in which cyclopropenone was utilized for the first time as the sole CO surrogate in the carbonylation process. Abstract : Herein we report a palladium-catalyzed [2 + 2 + 1] annulation among 3-iodochromones, bridged olefins, and cyclopropenone, giving a variety of chromone fused cyclopentanones that are of interest in medicinal chemistry. This protocol involves a Heck coupling/C(sp 2 )–H activation/carbonylation sequence, forming two C(sp 2 )–C(sp 3 ) bonds and a C(sp 2 )–C(sp 2 ) bond as well as a cyclopentanone unit in a single operation. Importantly, cyclopropenone in this methodology was utilized for the first time as the sole CO surrogate in the carbonylation process; its exceptional potential in carbonylation will be an inspiration for organic chemists.